Data skills for librarians: an overview of the Library Carpentry curriculum - Halvarsson, E; Southall, J (Bodleian Libraries, University of Oxford, 2022)
The Carpentries is an international organisation which teaches data and software skills to researchers and librarians. The Library Carpentries curriculum has been developed to help librarians ease their workloads, by automating repetitive tasks such as data cleaning and formatting. This session provides an overview of what Library Carpentry is and upcoming Carpentry training events. Note that all Carpentries lessons are aimed at beginners – so no previous background knowledge of coding is required to participate.